2014
DOI: 10.2141/jpsa.0130058
|View full text |Cite
|
Sign up to set email alerts
|

Preference and Passage through the Gastrointestinal Tract of Paddy Rice in Young Chicks

Abstract: Rice grain for feed has been used for chicken feed as a substitute for corn, since the nutritive values of corn and rice are similar. However, it is unclear whether rice grain for feed should be available for young chicks from the early stages of ages. It was reported that the preference for unpolished rice was low, but no information was available for paddy rice (PR) which is low in digestibility. In the present study, therefore, preference for PR and the passage of feed through the gastrointestinal tract wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…results of Nóbrega et al (2020). The average in this study was 32 min similar to the results obtained by Nóbrega et al (2020), who found that Japanese quails have the shortest time between entry and exit of food in the GIT when compared with other production birds such as broilers having a FAT of 80 to 90 min (Almirall & Esteve-Garcia, 1994;Yamanaga & Furuse, 2014) and commercial layers from 155 to 193 min (Mateos et al, 1982;Rougière & Carré, 2010).…”
Section: Determination Of the Gastrointestinal Passage Rate Using Dex...supporting
confidence: 88%
“…results of Nóbrega et al (2020). The average in this study was 32 min similar to the results obtained by Nóbrega et al (2020), who found that Japanese quails have the shortest time between entry and exit of food in the GIT when compared with other production birds such as broilers having a FAT of 80 to 90 min (Almirall & Esteve-Garcia, 1994;Yamanaga & Furuse, 2014) and commercial layers from 155 to 193 min (Mateos et al, 1982;Rougière & Carré, 2010).…”
Section: Determination Of the Gastrointestinal Passage Rate Using Dex...supporting
confidence: 88%
“…Under the trend of increasing global demand for corn, poultry producers are being forced to seek local raw materials to replace corn in animal feed. A large number of researchers have investigated the effect of different feed ingredients on the performance of poultry such as rice bran [ 1 , 2 ], defatted rice bran [ 3 , 4 ], paddy rice [ 5 , 6 , 7 ], whole wheat [ 8 , 9 , 10 ] and millet [ 11 , 12 , 13 ]. China is the largest rice producer in the world, accounting for 27.63% of global rice production [ 14 ].…”
Section: Introductionmentioning
confidence: 99%